Contribution of Groundwater to River Discharge in the Mampang Sub-watershed - Riana Palupi; Agus M. Ramdhan; Rusmawan Suwarman (International Journal of Science and Society, 2023)
Water is a necessity of human life. In fulfilling this need, the use of groundwater is often used. Groundwater is a non-renewable resource. Jakarta is a city traversed by many rivers and has a morphological dependence on the upstream watershed (DAS) in the Jabodetabek Region. The research location is in the Mampang Sub-watershed, which is in the Jakarta and Depok areas. The Mampang sub-watershed is geographically located at 106°48'44" - 106°49'59" East Longitude and 6°15'4" - 6°22'17" South Latitude. The problem in the research of the Mampang Sub-watershed often experiences floods every year with a height of between 10 cm - 50 cm. The aim of the study was to determine the groundwater-surface water interaction during a flood event at the study site. The method used is by collecting primary data and secondary data, then simulating using SWAT (Soil and Water Assessment Tools) and SWAT-MODFLOW. The SWAT MODFLOW simulation results obtained 874 river grids with Groundwater Surface Water Exchange Rates (GWSER) values in February 2020 between 52 m3/day to 353 m3/day and in September 2019 between -74 m3/day to 26 m3/day. The contribution of groundwater can be analyzed by comparing the river discharge in a certain month with the GSWER value for that month. The contribution of groundwater to the monthly peak discharge of the river at the study site ranges from 0.24% to 5.27%, and the average contribution of groundwater is 2.48%.